Features of the profession loss crisis in older teachers - E. E. Symanyuk; G. I. Borisov; A. A. Pecherkina; V. V. Saveliev (Russian State Vocational Pedagogical University, 2022)
Introduction. The relevance of the current research in the features of the profession loss crisis among older teachers is due to the need to develop the methods of psychological support for their professional development in the conditions of growing demands on the educational process.The aim of the study is to identify the features of the profession loss crisis among older teachers.In the course of the study, the authors put forward the following hypotheses. The features of the profession loss crisis include two scenarios, which are reflected in the psychological state of teachers and their attitude towards their own profession. The positive scenario is characterized by physical and psychological health, hardiness and psychological well-being, while the negative scenario is characterised by deterioration in physical and mental health, reduced hardiness and psychological well-being.Methodology and research methods. The methodological basis for the study was the concept of professional development by E. F. Zeer and E. E. Symaniuk, as well as the approaches to examining the psychological characteristics of the crisis of late age; psycho-aging changes at a later age; stages of professional development; features of experiencing crises. The study involved 956 teachers working in educational organisations of the Sverdlovsk region (58 men and 898 women). The average age of the respondents was 57.9 years. The features of the profession loss crisis were determined using the biographical method, which allowed the authors to consider the dynamic process of professional development and highlight the psychological characteristics of the crisis based on content analysis. The biographical questionnaire contained questions aimed at identifying general social and professional information, determining the characteristics of options, professional activities, retirement and plans for future life, as well as determining the success of a professional biography. The following methods were used: test of hardiness in the adaptation of E. N. Osin and E. I. Rasskazova; method of quality-of-life SF-36; T. V. Kornilova's new questionnaire of tolerance to uncertainty; scale of psychological well-being by K. Riff as adapted by T. D. Shevelenkova, P. P. Fesenko; questionnaire by K. Zamfir "Motivation of professional activity" in the modification of A. A. Rean. Data processing was carried out in the RStudio program. To highlight the options for the course of the crisis, cluster analysis was used. Welch's t-test was applied to compare the groups with each other. The one-sample Student's t-test was used to compare groups with standard indicators.Results. It was revealed that the profession loss crisis can proceed according to two scenarios, each of which has its own characteristics.In a positive scenario (about 3/4 of cases), the indicators of physical and psychological health, vitality and psychological well-being do not differ from the normative values. At the same time, teachers generally have a good attitude towards their profession and have plans to continue working in profession and learning something new.In the negative scenario of the crisis, the indicators of resilience and psychological well-being are at the lower limit of the norm, and the indicators of physical and mental health are significantly lower than the norm. Teachers are much more likely to note disappointment in the profession and, in general, have a more negative attitude towards it than the representatives of the positive group. Among them, there are significantly more of those who plan to leave the profession and fewer of those who plan to stay in the profession and learn something new.Scientific novelty consists in the enrichment of psychological science with knowledge about the features of the profession loss crisis among older teachers working at different levels of education in the context of the professional development of the individual.Practical significance. The presented results can be employed in educational organisations to develop programmes for the prevention of the profession loss crisis among teachers and recommendations for teachers of late maturity to maintain their active professional longevity.